Simplified design of steel structures - Ambrose, James E.; Ambrose, James ;Tripeny, Patrick (New Jersey : John Wiley & Son, Inc., 2007)
Updated to conform with current building codes, design practices, and industry standards, Simplified Design of Steel Structures uses the latest AMA Institute of Steel Construction (AISC) method of structural design.
Preface to the Eighth Edition. Preface to the First Edition. Introduction. 1 Considerations for Use of Steel. 1.1 Properties of Steel. 1.2 Types of Steel Products. 1.3 Development of Structural Systems. 1.4 Connection Methods. 1.5 Data for Steel Products. 1.6 Usage Considerations for Steel Structures. 1.7 Choice and Planning of Steel Structural Systems. 2 Structural Investigation and Design. 2.1 Situations for Investigation and Design. 2.2 Methods of Investigation and Design. 2.3 Investigation of Columns and Beams. 2.4 Investigation of Column and Beam Frames. 2.5 Approximate Investigation of Indeterminate Structures. 2.6 Service Conditions. 2.7 Limit States Versus Service Conditions. 2.8 Resistance Factors. 2.9 Choice of Design Method. 3 Horizontal-Span Framing Systems. 3.1 Factors in Beam Design. 3.2 Inelastic Versus Elastic Behavior. 3.3 Nominal Moment Capacity of Steel Beams. 3.4 Design for Bending. 3.5 Design of Beams for Buckling Failure. 3.6 Shear in Steel Beams. 3.7 Deflection of Beams. 3.8 Safe Load Tables. 3.9 Manufactured Trusses for Flat Spans. 3.10 Decks with Steel Framing. 3.11 Concentrated Load Effects in Beams. 3.12 Torsional Effects. 3.13 Buckling of Beams. 3.14 Beam Bearing Plates. 4 Steel Columns. 4.1 Column Shapes. 4.2 Slenderness and End Conditions. 4.3 Safe Axial Loads for Steel Columns. 4.4 Design of Steel Columns. 4.5 Columns with Bending. 4.6 Column Framing and Connections. 4.7 Column Bases. 5 Frame Bents. 5.1 Development of Bents. 5.2 Multiunit Rigid Frames. 5.3 Three-Dimensional Frames. 5.4 Mixed Frame and Wall Systems. 5.5 Special Problems of Steel Rigid Frame Bents. 5.6 Trussed Frames. 6 Miscellaneous Steel Components and Systems. 6.1 Manufactured Systems. 6.2 Composite Structural Elements. 6.3 Tension Elements and Systems. 7 Horizontal-Span Steel Trusses. 7.1 General Considerations. 7.2 Bracing for Trusses. 7.3 Loads on Trusses. 7.4 Investigation for Internal Forces in Planar Trusses. 7.5 Design Forces for Truss Members. 7.6 Combined Actions in Truss Members. 7.7 Design Considerations for Steel Trusses. 7.8 Two-Way Trusses. 8 Steel Connections. 8.1 Basic Considerations. 8.2 Bolted Connections. 8.3 Design of a Bolted Connection. 8.4 Bolted Framing Connections. 8.5 Bolted Truss Connections. 8.6 Welding. 8.7 Design of Welded Connections. 8.8 Welded Steel Frames. 8.9 Control Joints: Design for Selected Behavior. 9 General Considerations for Building Structures. 9.1 Choice of Building Construction. 9.2 Structural Design Standards. 9.3 Loads for Structural Design. 9.4 Dead Loads. 9.5 Building Code Requirements for Structures. 9.6 Live Loads. 9.7 Lateral Loads (Wind and Earthquake). 9.8 Load Combinations and Factors. 9.9 Determination of Design Loads. 9.10 Structural Planning. 9.11 Building Systems Integration. 9.12 Economics. 10 Building Structures: Design Examples. 10.1 Building One. 10.2 Building Two. 10.3 Building Three. 10.4 Building Four. 10.5 Building Five. 10.6 Building Six. Appendix A: Properties of Structural Sections. Appendix B: Beam Design Aids. Appendix C: Study Aids. Terms. Questions. Answers to Questions. Appendix D: Answers to Problems in Chapters. References. Index.
Includes bibliographical references.
Keywords: BUILDING, IRON AND STEEL